Antibacterial mechanisms of Aronia melanocarpa (Michx.), Chaenomeles superba Lindl. and Cornus mas L. leaf extracts. (15th July 2021) - Efenberger-Szmechtyk, Magdalena; Nowak, Agnieszka; Czyżowska, Agata; Śniadowska, Monika; Otlewska, Anna; Żyżelewicz, Dorota
Highlights: The leaf extracts decrease bacteria viability. The leaf extracts act as prooxidants to increase ROS generation in bacteria cells. The leaf extracts reduce bacteria membrane integrity. The leaf extracts cause morphological changes in bacteria cells. The leaf extracts inhibit DNA gyrase activity. Abstract: The aim of this study was to investigate the in vitro antibacterial mechanisms of Aronia melanocarpa, Chaenomeles superba, and Cornus mas leaf extracts towards meat spoilage and pathogenic bacteria. The extracts decreased bacterial viability after 24 h and 48 h of incubation. Acting as prooxidants, the extracts induced intracellular ROS (reactive oxygen species) generation in bacteria cells, with C. mas having the strongest influence. The leaf extracts increased the release of UV intracellular absorbing components, suggesting a reduction in membrane integrity. They also increased the outer-membrane permeability of the Gram-negative bacteria, with C. superba extract being the most active. Following exposure to the leaf extracts, morphological changes in the bacteria were observed, including the formation of aggregates, EPS synthesis, irregular forms, wrinkled cell surfaces, pores in the cell wall, and shriveling of cells. The leaf extracts inhibited DNA synthesis in E. coli cells by suppressing DNA gyrase activity.